Rebuilding Ukraine's infrastructure after the war - Iryna Kosse (The Vienna Institute for International Economic Studies (wiiw), 2023)
Ukraine is a big country with a developed multimodal transport infrastructure that includes a network of roads, railways, airports and seaports, as well as pipelines. In addition, the country has significant infrastructure for electricity generation and distribution, and for gas transportation. Ukraine is an urbanised country, with 46% of its population living in an apartment. The ongoing armed aggression by the Russian Federation has had a significant impact on Ukrainian infrastructure, leading to the destruction of roads, rail tracks, power stations and housing units. Over the next few years, the infrastructure sector will require significant financing, prioritisation and coordination between the Ukrainian government and international actors, based on the principles of multimodality, flexibility, connectivity and sustainable urban mobility. Energy and housing infrastructure should rely on renewable energy sources, distributed generation and energy-efficient housing. In addition, domestic infrastructure policies should be combined with EU infrastructure initiatives.
Keywords: R4; Q4; O1; O4; R1; H7; 330; Ukraine; multimodal transport infrastructure; electricity generation; electricity distribution; gas transportation; Russian Federation; infrastructure destruction; EU infrastructure initiatives